Mycosis fungoides and Sézary syndrome: clinical presentation, diagnosis, staging, and therapeutic management - Miyashiro, Denis; Sanches, José Antonio (Frontiers in Oncology, 2023)
Mycosis fungoides (MF) and Sézary syndrome (SS) are cutaneous T-cell lymphomas. MF is the most common cutaneous lymphoma, and it is classified into classic Alibert-Bazin MF, folliculotropic MF, pagetoid reticulosis, and granulomatous slack skin, each with characteristic clinical presentation, histological findings, and distinct clinical behaviors. SS is an aggressive leukemic variant of cutaneous lymphoma, and it is characterized by erythroderma, lymphadenopathy, and peripheral blood involvement by malignant cells. There is a wide range of dermatological manifestations of MF/SS, and prompt recognition is essential for early diagnosis. Skin biopsy for histology and immunohistochemistry analysis is imperative to confirm the diagnosis of MF/SS. Histology may also provide information that may have an impact on prognosis and treatment. Staging follows the TNMB system. Besides advanced staging, other factors associated with poorer prognosis are advanced age, male gender, folliculotropism in histology, large cell transformation, high expression of CD30 and Ki67, and elevated lactate dehydrogenase. Treatment is divided into skin-directed therapies (topical treatments, phototherapy, radiotherapy), and systemic therapies (biological response modifiers, targeted therapies, chemotherapy). Allogeneic bone marrow transplantation and extracorporeal photopheresis are other treatment modalities used in selected cases. This review discusses the main clinical characteristics, the histology/immunohistochemistry findings, the staging system, and the therapeutic management of MF/SS.